Adipocytokines in Cardiovascular and Metabolic Diseases - Ouchi, Noriyuki (J Atheroscler Thromb, 2016)
Obesity, particularly excess visceral fat accumulation, is highly associated with the development of metabolic syndrome and atherosclerotic cardiovascular disease. Adipose tissue produces a variety of secreted proteins, referred to as adipocytokines, which directly affect nearby or remote organs. Dysregulation of adipocytokines caused by obese conditions contributes to the pathogenesis of various metabolic and cardiovascular disorders. This review focuses on the significance of several adipocytokines that potentially exert beneficial actions on obesity-related diseases, including atherosclerosis and ischemic heart disease.